Kepemimpinan Pendidikan Islam Perspektif Suku - Selva Susila Oktoberia (Ahad: Multidisciplinary Journal of Islamic Studies, 2025)
This article aims to examine the values ​​of leadership in Islamic education from the perspective of tribes, especially the Quraysh tribe, which is known to have a strong social structure, cultural values, and leadership since before the arrival of Islam. This study uses a descriptive qualitative method with a library research approach and internet searches for relevant literature that discusses leadership and education in the context of Islam. The results of the study show that the Quraysh tribe has made a major contribution to shaping the character and system of Islamic leadership, with values ​​such as trustworthiness, honesty, deliberation, moral exemplars, and social responsibility that are strengthened through Islamic teachings. Quraysh figures such as the Prophet Muhammad SAW, Abu Bakar, Umar bin Khattab, and others are role models in Islamic educational leadership, both in the formation of educational institutions, teaching, and preserving Islamic teachings. The leadership values ​​of the Quraysh tribe remain relevant and can be used as inspiration in answering the challenges of Islamic educational leadership in the modern era.